Catastrophic Decline in Women's Ownership of Firms in India, 2014 and 2022 - Pal, Rupayan; 2024; Kumari, Rozi (Economic and Political Weekly, 2024)
Analysing nationally representative data sets from the World Bank Enterprise Surveys, women's ownership and participation in top management of registered private firms in India are examined. It is seen that both the parameters have drastically decreased, from a low to a meagre level between 2014 and 2022, despite sustained gross domestic product growth and the launch of several government programmes to promote entrepreneurship. The pattern of decline is consistent across sectors (manufacturing and services) and size groups (small, medium, and large) of firms, barring some variations. This is true regardless of the measure of women's ownership considered and is not due to the entry and exit of firms.
Keywords: Catastrophic; Domestic Product Growth; Women's Ownership; Entrepreneurship